2019
DOI: 10.3390/nano9070969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Graphene Oxide Induced Cellular Toxicity and Transcriptome Analysis in Human Embryonic Kidney Cells

Abstract: Graphene, a two-dimensional carbon sheet with single-atom thickness, shows immense promise in several nanoscientific and nanotechnological applications, including in sensors, catalysis, and biomedicine. Although several studies have shown the cytotoxicity of graphene oxide in different cell types, there are no comprehensive studies on human embryonic kidney (HEK293) cells that include transcriptomic analysis and an in vitro investigation into the mechanisms of cytotoxicity following exposure to graphene oxide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 68 publications
(101 reference statements)
1
41
0
Order By: Relevance
“…40 RNA-sequencing data analysis by Gurunathan et al revealed that GO, through changingexpression of genes involved in apoptosis-related biological pathways in HEK293 cells, triggered apoptosis and cell death, in agreement with our results. 42 Tang et al showed that exposing K7M2 cells to GO increased cell apoptosis due to generation of ROS, confirmed our apoptosis-and ROS-assay results, as more ROS generation led to higher levels of apoptosis. 43 Cell cycle-analysis also showed a block in the G 2 /M phase in GO-treated groups, but the pattern for 200 µg/mL nGO was completely different, as this treatment increased the G 2 /M phase more than the control group.…”
Section: Discussionsupporting
confidence: 87%
“…40 RNA-sequencing data analysis by Gurunathan et al revealed that GO, through changingexpression of genes involved in apoptosis-related biological pathways in HEK293 cells, triggered apoptosis and cell death, in agreement with our results. 42 Tang et al showed that exposing K7M2 cells to GO increased cell apoptosis due to generation of ROS, confirmed our apoptosis-and ROS-assay results, as more ROS generation led to higher levels of apoptosis. 43 Cell cycle-analysis also showed a block in the G 2 /M phase in GO-treated groups, but the pattern for 200 µg/mL nGO was completely different, as this treatment increased the G 2 /M phase more than the control group.…”
Section: Discussionsupporting
confidence: 87%
“…In this work, we aimed to determine the effects of mono-GO and multi-GO on DCs using in vitro cell model. According to bioapplication and various toxicity studies of GO (Shao et al, 2017;Hoyle et al, 2018;Pelin et al, 2018;Gurunathan et al, 2019a), we finally selected concentrations of 0.01 mg/ml, 0.1 mg/ml, 1 mg/ml, 10 mg/ml, and 100 mg/ml for in vitro toxicity tests. Here, our results showed mono-GO is less toxic to DCs than multi-GO.…”
Section: Discussionmentioning
confidence: 99%
“…GO and its derivatives are of immense interest to nanomedicine researchers due to their remarkable electronic, mechanical and thermal properties [113]. GO is widely used as an antibacterial and anticancer agent [114]. GO act as antiviral agent through inactivation of the pathogenic agent of hand-foot-and-mouth disease, EV71 and endemic gastrointestinal avian influenza A virus H9N2 [115].…”
Section: Graphene Oxidementioning
confidence: 99%